Induced Phenotype Targeted Therapy: Radiation-Induced Apoptosis-Targeted Chemotherapy. (12th December 2014) - Lee, Beom Suk; Cho, Yong Woo; Kim, Gui Chul; Lee, Do Hee; Kim, Chang Jin; Kil, Hee Seup; Chi, Dae Yoon; Byun, Youngro; Yuk, Soon Hong; Kim, Kwangmeyung; Kim, In-San; Kwon, Ick Chan; et al.
Abstract : Background: Tumor heterogeneity and evolutionary complexity may underlie treatment failure in spite of the development of many targeted agents. We suggest a novel strategy termed induced phenotype targeted therapy (IPTT) to simplify complicated targets because of tumor heterogeneity and overcome tumor evolutionary complexity. Methods: We designed a caspase-3 specific activatable prodrug, DEVD-S-DOX, containing doxorubicin linked to a peptide moiety (DEVD) cleavable by caspase-3 upon apoptosis. To induce apoptosis locally in the tumor, we used a gamma knife, which can irradiate a very small, defined target area. The in vivo antitumor activity of the caspase-3–specific activatable prodrug combined with radiation was investigated in C3H/HeN tumor-bearing mice (n = 5 per group) and analyzed with the Student's t test or Mann-Whitney U test. All statistical tests were two-sided. We confirmed the basic principle using a caspase-sensitive nanoprobe (Apo-NP). Results: A single exposure of radiation was able to induce apoptosis in a small, defined region of the tumor, resulting in expression of caspase-3. Caspase-3 cleaved DEVD and activated the prodrug. The released free DOX further activated DEVD-S-DOX by exerting cytotoxic effects on neighboring tumor or supporting cells, which repetitively induced the expression of caspase-3 and the activation of DEVD-S-DOX. This sequential and repetitive process propagated the induction of apoptosis. This novel therapeutic strategy showed not only high efficacy in inhibiting tumor growth (14-day tumor volume [mm 3 ] vs radiation alone: 848.21±143.24 vs 2511.50±441.89, P < .01) but also low toxicity to normal cells and tissues. Conclusion: Such a phenotype induction strategy represents a conceptually novel approach to overcome tumor heterogeneity and complexity as well as to substantially improve current conventional chemoradiotherapy with fewer sequelae and side effects.